THE ROLE OF PEDAGOGICAL INNOVATIONS IN IMPROVING THE QUALITY OF EDUCATIONAL SERVICES IN THE CONTEXT OF GLOBALIZATION (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article explores the vital role of pedagogical innovations in improving the quality of educational services in the context of globalization. In today’s rapidly changing world, globalization is reshaping not only economies and cultures but also educational systems. As countries become more interconnected, educational institutions face increasing pressure to meet international standards, integrate modern technologies, and prepare students for global competitiveness. In this environment, traditional teaching approaches are often insufficient, making pedagogical innovation a key factor in ensuring quality and relevance in education. The article analyzes how innovative teaching methods such as student-centered learning, digital technologies, blended and online learning, project-based learning, and competency-based education contribute to enhancing learning outcomes and developing critical 21st-century skills. Particular attention is given to the role of information and communication technologies (ICT), interactive platforms, and artificial intelligence in transforming teaching and assessment practices. The study emphasizes that innovation in pedagogy is not limited to technology alone, but also includes changes in curriculum design, assessment strategies, teacher professional development, and institutional management.